The Effect of Molecular Weight on the Antimicrobial Activity of Chitosan from Loligo opalescens for Food Packaging Applications - Luciana C. Gomes; Sara I. Faria; Jesus Valcarcel; José A. Vázquez; Miguel A. Cerqueira; Lorenzo Pastrana; Ana I. Bourbon; Filipe J. Mergulhão (Marine Drugs, 2021)
The growing requirement for sustainable processes has boosted the development of biodegradable plastic-based materials incorporating bioactive compounds obtained from waste, adding value to these products. Chitosan (Ch) is a biopolymer that can be obtained by deacetylation of chitin (found abundantly in waste from the fishery industry) and has valuable properties such as biocompatibility, biodegradability, antimicrobial activity, and easy film-forming ability. This study aimed to produce and characterize poly(lactic acid) (PLA) surfaces coated with β-chitosan and β-chitooligosaccharides from a Loligo opalescens pen with different molecular weights for application in the food industry. The PLA films with native and depolymerized Ch were functionalized through plasma oxygen treatment followed by dip-coating, and their physicochemical properties were assessed by Fourier-transform infrared spectroscopy, X-ray diffraction, water contact angle, and scanning electron microscopy. Their antimicrobial properties were assessed against Escherichia coli and Pseudomonas putida, where Ch-based surfaces reduced the number of biofilm viable, viable but nonculturable, and culturable cells by up to 73%, 74%, and 87%, respectively, compared to PLA. Biofilm growth inhibition was confirmed by confocal laser scanning microscopy. Results suggest that Ch films of higher molecular weight had higher antibiofilm activity under the food storage conditions mimicked in this work, contributing simultaneously to the reuse of marine waste.